IMPLEMENTASI MODEL CONTEXTUAL TEACHING AND LEARNING PADA PEMBELAJARAN TEMATIK - Rina Rahmi; Safrida; M. Syahril Ramadhan; Sari Paton Marziah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to examine more deeply about the contextual teaching learning model in order to find information related to the model in question. This study uses a descriptive qualitative approach, namely understanding the phenomenon of what is experienced by researchers with the aim of obtaining complete information by collecting various data sources. The data sources used are primary and secondary data sources. Primary data sources are in the form of observations and interviews with teachers, students and school principals, while secondary data sources include documentation, scientific journals, books and the like which researchers can use to obtain information. The data obtained, analyzed using policy research. The results of the study found that through the application of the contextual teaching learning model, it can increase student learning activeness, student-centered learning, and gain knowledge that is dynamic and flexible. In addition, the application of the contextual teching learning model also shows the interaction and cooperation carried out by parents and the school to create quality students as observers of future education. Thus, this contextual teaching learning model is highly recommended to be applied in the ongoing learning process